Deregulation and Targeting of TP53 Pathway in Multiple Myeloma - Jovanović, Katarina K.; Escure, Guillaume; Demonchy, Jordane; Willaume, Alexandre; Van de Wyngaert, Zoe; Farhat, Meryem; Chauvet, Paul; Facon, Thierry; Quesnel, Bruno; Manier, Salomon (Frontiers in Oncology, 2019)
Multiple Myeloma (MM) is an incurable disease characterized by a clonal evolution across the course of the diseases and multiple lines of treatment. Among genomic drivers of the disease, alterations of the tumor suppressor TP53 are associated with poor outcomes. In physiological situation, once activated by oncogenic stress or DNA damage, p53 induces either cell-cycle arrest or apoptosis depending on the cellular context. Its inactivation participates to drug resistance in MM. The frequency of TP53 alterations increases along with the progression of the disease, from 5% at diagnosis to 75% at late relapses. Multiple mechanisms of regulation lead to decreased expression of p53, such as deletion 17p, TP53 mutations, specific microRNAs overexpression, TP53 promoter methylations and MDM2 overexpression. Several therapeutic approaches aim to target the p53 pathway, either by blocking its interaction with MDM2 or by restoring the function of the altered protein. In this review, we describe the mechanism of deregulation of TP53 in MM, its role in MM progression and the therapeutic options to interact with the TP53 pathway.